Analgesia and Sedation in Newborns with Long-Term Mechanical Ventilation - Evgenii V. Shestak; Olga P. Kovtun ("Paediatrician" Publishers LLC, 2023)
Relevant data on drugs used for analgesia and sedation in newborns in the intensive care units during mechanical ventilation is presented. The overview of studies on the most common sedatives and analgesics (opioids, acetaminophen, ketamine, midazolam, dexmedetomidine, propofol) is provided. Analysis of their efficacy and risk of short-term and long-term adverse effects is presented, including those associated with the child's nervous system development. The use of drugs both as monotherapy and in combination with other medications for analgesia and sedation is being discussed.